Fire Exit - Talty, Morgan ([Place of publication not identified] : Tin House Books, 2024)
"Utterly consuming. . . . Fire Exit absolutely smolders."--Tommy Orange The blood that came out of me was blood that ran through her veins. It's strange: all bloodlooks the same, yet it's different, we're told, in so many various ways and for so many various reasons. But one thing is for certain, I thought: you are who you are, even if you don't know it.
new book 2024 summer.
Keywords: Indigenous; Family life; Secrecy; Fathers; Cultural Heritage